Trouble with Marriage feminists confront law and violence in India - Basu, Srimati (Hyderabad, 2015)
The Trouble with Marriage considers the legacies of legal reforms around marriage and gendered violence in India in the 1980s which were strongly influenced by demands of the women’s movement: lawyer-free Family Courts, the criminal prosecution of domestic violence, rape law reform, and the promotion of alternate dispute resolution as a mode of better gendered access. Looking backward to legislative debates, and forward to everyday life in legal sites of marital trouble, such as Family Court, police cells for women, and mediation organizations, it presents a portrait of contemporary marriage and of legal culture. New legal subjectivities and strategies emerge as men and women negotiate concerns with money, kinship and violence in formal and informal venues, using a range of potentially contradictory civil and criminal laws. Some laws become popular in ways not imagined as part of their feminist scope: Family Courts proffer reconciliation as optimal solution, rape law secures marriage by evacuating consent as a criterion; domestic violence claims help with better economic settlements while rendering violence invisible. Through compelling ethnographic vignettes and a re-evaluation of feminist theories of law, marriage, violence, property, and the state, Basu argues that despite reforms, legal process reproduces the profound structural vulnerabilities generated by marriage. Alternative dispute resolution, designed to empower women in a less adversarial legal environment, has created new subjectivities, but, paradoxically, also reinforces oppressive socioeconomic norms. This book would be of interest to those in Law and Society Studies, Gender / Women’s Studies, Anthropology, Sociology, and to those activists and NGOs who work on gender, marriage and violence.